COMPARATIVE STUDY OF DIFFERENT ANAND-BHAIRAV RASA AND ITS STANDARIZATION (W.S.R. TO BHAISHAJYA RATNAVALI) - Verma, *Deepika; Pandey, Priyanka; Sharma, Usha; Dr, Rajnikant (International Journal of Ayurveda and Pharma Research, 2018)
Introduction: Standardization of Ayurvedic drug is an important criteria for selection, processing, efficacy & safety wise, to meet the WHO guidelines for the world wide acceptability of Ayurvedic formulations. Therefore different preparations of Anandbhairav rasa from classic Bhaishajya Ratnavali has been selected and studied for standariztion.Materials & Methods: Three samples of Anand Bhairav Rasa were prepared according to Jwaratisar prakaran of Bhaishajya Ratnavaliand three samples according to Atisar Prakaran of Bhaishajya Ratnavali were made and subjected to various physico-chemical analyses so that their physical as well as chemical changes can be analyzed.Conclusion: Both formulations showed the difference in pharmaceutically, organoleptic examination as well as in chemical analysis. However, the results obtained from physico chemical analysis of all the three samples are very close together and within fixed physico-chemical norms as described in pharmacopeial standards for Ayurvedic formulations.